Den ideelle leder: Resultatorienteret analytiker eller empatisk kommunikator? - Holmgreen, Lise-Lotte (Academic Quarter | Akademisk kvarter, 2013)
Den ideelle leder. How is the ideal leader constructed in the Danish corporate sector? Is it the result-oriented and dynamic analyst or the empathic and collaborative communicator who is in demand? Both types exist, but the analysis of management job ads from the Danish job databases, Stepstone and Job Index, indicates that the first type is more in demand among Danish businesses than the second one (Holmgreen, manuscript). Taking the starting point in framing (Evans & Green 2006; Fillmore 1982; Kövecses 2006; Lakoff 1987, 1996), the article analyses a corpus of Danish job ads, uncovering how leaders and leadership are constructed discursively, how this construction is conceptually rooted in culturally contingent frames of the competent leader (cf. Dickson et al. 2012), and not least how this construction may influence recruitment to management positions in the Danish business sector.